Teacher Perceptions: Principal Leadership, Teacher Discipline and Their Influence on Teacher Performance - maisinur, elza; Rosidin, Undang (Journal of Advanced Islamic Educational Management, 2022)
The purpose of this study is to determine the impact of madrasa principal leadership and discipline on teacher performance at Baitul Muslim Integrated Islamic Elementary School Way Jepara, Lampung Timur, Indonesia. Correlational research design is used to test the strength or weakness of the relationship between perceptions of principal leadership, and teacher work discipline, with teacher performance. this research is a population study. The research data were collected using questionnaires and documentation methods. The research data were analyzed using the descriptive quantitative analysis method with the calculation of Pearson correlation (product-moment) with the help of SPSS version 21. The results of the study show that there is a positive and significant influence between teachers' perceptions of the leadership of principals and teacher performance at Baitul Muslim Integrated Islamic Elementary School Way Jepara, Lampung Timur, Indonesia,. There is a positive and significant influence between work discipline and teacher performance at Baitul Muslim Integrated Islamic Elementary School Way Jepara, Lampung Timur, Indonesia. The achievement or improvement of teacher performance is largely determined by teachers' perceptions of the principal's leadership and work discipline. The results of the analysis show that discipline is one of the factors originating from internal teachers that support the improvement of teacher performance. Good discipline will have a maximum impact and encourage teachers to maximize their performance.